Prognostic value of left atrial reservoir function in patients with severe primary mitral regurgitation undergoing mitral valve repair - Stassen Jan; van Wijngaarden Aniel L; Butcher Steele C; Palmen Meindert; Herbots Lieven; Bax Jeroen J; Delgado Victoria; Marsan Nina Ajmone (OXFORD UNIV PRESS, 2022)
Aims: Mitral regurgitation (MR) has a significant haemodynamic impact on the left atrium. Assessment of left atrial reservoir strain (LARS) may have important prognostic implications, incremental to left atrial (LA) volume, and conventional parameters of left ventricular (LV) structure and function. This study investigated whether preoperative assessment of LARS by speckle tracking echocardiography is associated with long-term outcomes in patients undergoing mitral valve repair for severe primary MR.
Methods and results: Echocardiography was performed prior to mitral valve surgery in 566 patients (age 64 +/- 12years, 66% men) with severe primary MR. The study population was subdivided based on a LARS value of 22%, using a spline curve analysis. The primary endpoint was all-cause mortality. During a median follow-up of 7 (4-12) years, 129 (22.8%) patients died. Patients with LARS <= 22% showed significantly higher mortality rates at 1-, 3-, and 5-year follow-up (6%, 12%, and 15%, respectively) when compared with patients with LARS >22% (2%, 3% and 5%, respectively, P < 0.001). Age [hazard ratio (HR): 1.06; 95% confidence interval (CI): 1.03-1.09; P < 0.001], LV global longitudinal strain (HR: 0.92; 95% CI: 0.87-0.98; P = 0.014), and LARS (HR: 0.96; 95% CI: 0.93-0.99; P = 0.014) were independently associated with all-cause mortality.
Conclusion: Preoperative LARS is independently associated with all-cause mortality in patients undergoing mitral valve repair for primary MR and provides incremental prognostic value over LA volume. LARS might be helpful to guide timing of mitral valve surgery in patients with severe primary MR.